Proteinase-activated receptors (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Proteinase-activated receptors (PARs, nomenclature as agreed by the NC-IUPHAR Subcommittee on Proteinase-activated Receptors [35]) are unique members of the GPCR superfamily activated by proteolytic cleavage of their amino terminal exodomains. Agonist proteinase-induced hydrolysis unmasks a tethered ligand (TL) at the exposed amino terminus, which acts intramolecularly at the binding site in the body of the receptor to effect transmembrane signalling. TL sequences at human PAR1-4 are SFLLRN-NH2, SLIGKV-NH2, TFRGAP-NH2 and GYPGQV-NH2, respectively. With the exception of PAR3, synthetic peptides with these sequences (as carboxyl terminal amides) are able to act as agonists at their respective receptors. Several proteinases, including neutrophil elastase, cathepsin G and chymotrypsin can have inhibitory effects at PAR1 and PAR2 such that they cleave the exodomain of the receptor without inducing activation of Gαq-coupled calcium signalling, thereby preventing activation by activating proteinases but not by agonist peptides. Neutrophil elastase (NE) cleavage of PAR1 and PAR2 can however activate MAP kinase signaling by exposing a TL that is different from the one revealed by trypsin [73]. PAR2 ectivation by NE regulates inflammation and pain responses [101, 65] and triggers mucin secretion from airway epithelial cells [102].